The Concept of Governmentality in Building the Conceptual Foundation for the Role of Internal Audit in Corporate Governance: Konsep Governmentality dalam Membangun Fondasi Konseptual Peran Audit Internal dalam Tata Kelola Perusahaan - Hanif, Aisha; Rini, Dina Dwi Oktavia; Rahayu, Duwi (Procedia of Social Sciences and Humanities, 2022)
The concept of supervision (panopticon) initiated by Michael Foucault explains how internal audit is used by management to encourage subjects to monitor themselves. The presence of internal audit produces patterns of employee behavior that make the discursive nature of the exercise of power clear. This interpretation was developed to conceptualize the preventive role of internal auditors in risk management. The concept of governmentality adopted from Foucauldian thought can facilitate the self-assessment of auditee controls used by internal auditors and is an integral part of tools to make subject matter manageable. This study aims to reveal the basic formulation of the internal auditor's strategy to maintain the auditee's trust in the internal auditor. The research method used is a qualitative research method using a phenomenological approach. The research findings state that the auditee has a perceived tendency to be suspicious of the role and function of the internal auditor, so that the auditee tends to be less able to cooperate or support the work of the internal auditor properly because internal audit activities are considered as a monitoring tool that has the effect of disrupting the routine activities of the organization.